Changing face of medical education during a pandemic: tragedy or opportunity?. Issue 1161 (30th June 2021) - Leong, Jean Mei Ching; Lam, Wee Leon; Tan, Shi Zhuan; Ng, Chye Yew
Abstract: The COVID-19 pandemic has changed forever the way we do certain things. Although the race for a cure and vaccine has taken centre stage, traditional face-to-face medical education has slowly metamorphosised in the background to a virtual world with innumerable webinars, virtual tutorials and lectures in the World Wide Web. Despite this seemingly 'perfect' solution, there remains a hidden cost. Educators are forced to learn new skills to engage students as well as manipulate the electronic platform. Impact on learning for students, both undergraduate and postgraduate from a lack of social interactions, remains unknown. In this article, the authors share their experiences from different specialities about the pros and cons of virtual learning and teaching. Suggestions and practical tips are offered to enhance the learning experience. More emphasis may need to be placed on the creation of learning communities rather than lecture-based curricula. Hybrid curricula or conferences may become the future norm. As we slowly move out of lockdown into a changed world and new ways of doing things, lessons learnt can be harnessed for future hybrid models that can combine the best of technology and physical teaching to reduce worldwide inequalities.